"ECO-ISLAM INTEGRATES ENVIRONMENTAL VALUES IN ISLAMIC EDUCATION LEARNING INNOVATION THROUGH THE GREEN MADRASAH MOVEMENT" - Sintiya, Sindy (Journal of Educational Science Learning and Research, 2025)
The global ecological crisis demands the active involvement of all sectors, including religious education. This article proposes the integration of environmental values in Islamic Religious Education (PAI) learning through the Green Madrasah concept. This study uses a descriptive qualitative approach with a case study in a madrasah aliyah in West Java. The results show that Islamic values such as khalifah fil ardh, amanah, and tazkiyatun nafs can be used as theological foundations in building students' environmental awareness. Through activities such as sharia waste banks, communal tree planting movements, and thematic PAI-LH curriculum, students experience an increase in environmental awareness and holistic understanding of religion. Green Madrasah has proven to be a relevant and contextual learning innovation. The increasingly acute environmental crisis demands a transformative educational approach rooted in spiritual values. This article aims to examine the integration of environmental values in Islamic Religious Education (PAI) learning through the development of the Green Madrasah concept as a pedagogical strategy. A descriptive qualitative approach with a case study method is used to examine the implementation of this program in one of the madrasah aliyah in West Java. The results of the study indicate that strengthening theological values such as khalifah fil ardh, amanah, and prohibition of facades are strong conceptual foundations in instilling ecological awareness in students. The implementation of the Green Madrasah program which includes sharia-based waste bank activities, collective tree planting, and integration of Islamic Religious Education and environmental curricula, has proven effective in forming religious character and love for the environment in students. This study recommends expanding the concept of Eco-Islam in the national education system as a response to the global ecological crisis.